DESIGN OF SHOOTING SCORE RECORDING INFORMATION SYSTEM BASED ON IMAGE PROCESSING - Choirur Rozikin; Fifin Kurnianto; Ahmadi Ahmadi; Mohammad Syaifi (JOURNAL ASRO, 2018)
Image processing shooter-based Information System is very useful for STTAL, which has a visionto become a center for the development of defense science and technology in the field of military,maritime and reliable seas at the regional level in realizing the independence of the main weaponssystem.STTAL has the mission of organizing higher education programs to produce human resourceswith Indonesian character and personality, based on science and technology that are of high quality andrelevant to the defense needs of the military, maritime and marine departures. In carrying out its duties asan educational institution, STTAL also carries out its obligations as the Indonesian National Army. So withthat STTAL often hold short barrel or pistol shooting exercises. In a series of short barrel or pistolshooting activities, each process of recording values is still carried out visually, that is by looking directlyat the target and counting manually, so that it takes a lot of members of the shooting committee and takesa long time in recording values. We design a application of image processing information system basedshots which can be used in shooting exercises to facilitate all members in carrying out shooting exercisesat STTAL. In this application the shooter can see firsthand the value of the shot obtained so that it canconcentrate fully in carrying out a shooting exercise. In this application also makes it easy for the head ofthe shooting committee to make a report to the commander quickly and accurately, for the commander tosee first hand the results of the shooting practice and it's easy to take a decision on shooting practice.Keywords: Value Marker, Shooting, Image Process.